2019
DOI: 10.1111/imb.12614
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional cellulase enzymes are ancestral in Polyneoptera

Abstract: Many hemimetabolous insects produce their own cellulase enzymes from the glycoside hydrolase family 9, first observed in termites and cockroaches. Phasmatodea have multiple cellulases, some of which are multifunctional and can degrade xylan or xyloglucan. To discover when these abilities evolved, we identified cellulases from the Polyneoptera sampled by the 1000 Insect Transcriptome and Evolution (1KITE) project, including all cockroach and termite transcriptomes. We hoped to identify what role enzyme substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Until now, hemicellulose degradation seems to be conducted by gut microbes, and no putative hemicellulolytic genes were recovered from the reconstructed termite transcriptome. For comparison, recent discovery of multi-functional GH9 cellulases in Phasmatodea suggested that some insects are capable to target xylan and xyloglucan in addition to cellulose 36 . The same study evidenced multi-functionality for two GH9 cellulases from Mastotermes darwiniensis, suggesting that some endogenous GH9 members in termites might also hydrolyse hemicellulose.…”
Section: Diet On Miscanthus: Who Does What?mentioning
confidence: 99%
“…Until now, hemicellulose degradation seems to be conducted by gut microbes, and no putative hemicellulolytic genes were recovered from the reconstructed termite transcriptome. For comparison, recent discovery of multi-functional GH9 cellulases in Phasmatodea suggested that some insects are capable to target xylan and xyloglucan in addition to cellulose 36 . The same study evidenced multi-functionality for two GH9 cellulases from Mastotermes darwiniensis, suggesting that some endogenous GH9 members in termites might also hydrolyse hemicellulose.…”
Section: Diet On Miscanthus: Who Does What?mentioning
confidence: 99%
“…For example, in the bean beetle Callosobruchus maculatus , a protein from the subfamily 10 of GH5 (GH5_10)—a typical family of mannanases—has been identified; this protein accepts only xylan as a substrate . In stick and leaf insects (Phasmatodea), a gene family encoding GH9 proteins expanded through several gene duplication events, resulting in one clade of orthologous GH9 proteins having the ability to use both amorphous cellulose and xylan as substrates . We expect that more insect‐derived xylanases will be identified in the near future, due to the increasing amount of transcriptome/genome data which are currently generated, in particular for phytophagous/xylophagous species.…”
Section: Discussionmentioning
confidence: 99%
“…xyloglucanolytic cellulase and a speci c ancestral cellulase that lacks cellulolytic ability in almost all the insect orders necessitate the critical investigation with expansion of enzyme hypothesis (Shelomi et al, 2020). These divergent approaches to the insect cellulases indicate its multifaceted potentialities that hold a strong stand in research pursuits.…”
Section: Discussionmentioning
confidence: 99%